Politicians' outside earnings and electoral competition - Johannes Becker; Andreas Peichl; Johannes Rincke (Finanzwissenschaftliches Forschungsinstitut an der Universität zu Köln (FiFo Köln), 2008)
This paper deals with the impact of electoral competition on politicians outside earnings. We propose a simple theoretical model with politicians facing a tradeoff between allocating their time to political effort or to an alternative use generating outside earnings. The model has a testable implication stating that the amount of time spent on outside work is negatively related to the degree of electoral competition. We test this implication using a new dataset on outside earnings of members of the German federal assembly. Taking into account the potential endogeneity of measures of political competition that depend on past election outcomes, we find that politicians facing low competition have substantially higher outside earnings.
Keywords: J45; D72; 330; Political competition; outside earnings; political rents; Politiker; Nebentätigkeit; Rent Seeking; Wahlkampf; Deutschland